Progress in the characterization of the gas jet target at IFUNAM. (22nd January 2015) - Favela, F; Chávez, E; de Lucio, O; Andrade, E; Ortíz, M E
Abstract: The windowless gas target (supersonic jet) at IFUNAM has been characterized using the Elastic Backscattering Spectrometry (EBS) technique with proton beams. Jets of Air, Nitrogen and Argon at different pressures were studied. Areal densities above 10 18 atoms/cm 2 have been achieved.